Rapid Presumptive Identification of Bacillus anthracis Isolates Using the Tetracore RedLine Alert™ Test - Pillai, Segaran P. (Health Secur, 2019)
A comprehensive laboratory evaluation of the Tetracore RedLine Alert test, a lateral flow immunoassay (LFA) for the rapid presumptive identification of Bacillus anthracis, was conducted at 2 different test sites. The study evaluated the sensitivity of this assay using 16 diverse strains of B. anthracis grown on sheep blood agar (SBA) plates. In addition, 83 clinically relevant microorganisms were tested to assess the specificity of the RedLine Alert test. The results indicated that the RedLine Alert test for the presumptive identification of B. anthracis is highly robust, specific, and sensitive. RedLine Alert is a rapid test that has applicability for use in a clinical setting for ruling-in or ruling-out nonhemolytic colonies of Bacillus spp. grown on SBA medium as presumptive isolates of B. anthracis.